1999
DOI: 10.1152/ajpregu.1999.277.5.r1392
|View full text |Cite
|
Sign up to set email alerts
|

Body fluid expansion is not essential for salt-induced hypertension in SS/Jr rats

Abstract: To evaluate the importance of volume in the development of hypertension in inbred Dahl salt-sensitive rats (SS/Jr), we measured the changes in blood pressure (BP) that occurred with oral intake of food (salt) and water in rats whose body weight was permitted to increase versus those in which body weight was maintained constant with a servo-control system. We hypothesized that if volume expansion is essential in the development of hypertension, then BP would not increase if body weight was held constant. We fou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
23
0
1

Year Published

2007
2007
2021
2021

Publication Types

Select...
3
3

Relationship

0
6

Authors

Journals

citations
Cited by 31 publications
(29 citation statements)
references
References 21 publications
5
23
0
1
Order By: Relevance
“…This observation suggests that, in some sult-sensitive humans, the plasma concentration of Na ϩ attained with Na ϩ loading may critically determine the extent of the pressor effect of dietary NaCl. The observation accords with observations that Qi et al 21 reported in the NaCl-loaded Dahl SS/Jr rat, in which BP varied directly and highly significantly with plasma Na ϩ concentration, irrespective of the hydration state orally imposed. Qi et al 21 proposed, as have others, 4,22,23 that "directly mediated increases in plasma Na ϩ can increase arterial BP in rats by mechanisms that are apparently not related to fluid volume changes."…”
Section: Schmidlin Et Al Sodium-selective Salt Sensitivitysupporting
confidence: 92%
See 3 more Smart Citations
“…This observation suggests that, in some sult-sensitive humans, the plasma concentration of Na ϩ attained with Na ϩ loading may critically determine the extent of the pressor effect of dietary NaCl. The observation accords with observations that Qi et al 21 reported in the NaCl-loaded Dahl SS/Jr rat, in which BP varied directly and highly significantly with plasma Na ϩ concentration, irrespective of the hydration state orally imposed. Qi et al 21 proposed, as have others, 4,22,23 that "directly mediated increases in plasma Na ϩ can increase arterial BP in rats by mechanisms that are apparently not related to fluid volume changes."…”
Section: Schmidlin Et Al Sodium-selective Salt Sensitivitysupporting
confidence: 92%
“…The observation accords with observations that Qi et al 21 reported in the NaCl-loaded Dahl SS/Jr rat, in which BP varied directly and highly significantly with plasma Na ϩ concentration, irrespective of the hydration state orally imposed. Qi et al 21 proposed, as have others, 4,22,23 that "directly mediated increases in plasma Na ϩ can increase arterial BP in rats by mechanisms that are apparently not related to fluid volume changes." An increase in plasma Na ϩ concentration may elicit a pressor effect by increasing cerebro-spinal fluid Na ϩ concentration 24 and by thereby activating central sympathoexcitatory mechanisms that give rise to increased sympathetic outflow.…”
Section: Schmidlin Et Al Sodium-selective Salt Sensitivitysupporting
confidence: 92%
See 2 more Smart Citations
“…Herein, we refer to salt-induced changes of this time course as 'acute' to distinguish them from much slower salt-induced effects discussed in subsequent sections. Acute salt sensitivity of blood pressure has been demonstrated in experiments involving a number of species including chickens, 19,20 dogs, [21][22][23][24] green monkeys, 25 mice, 26 pigs, 27 rabbits, 28,29 rats [30][31][32][33][34] and spider monkeys. 25,35 An example of the time course of the blood pressure response to a high-salt diet in regular Sprague-Dawley rats is shown in Figure 2.…”
Section: Acute Salt Sensitivity Of Blood Pressurementioning
confidence: 99%